Sistem Pendukung Keputusan Menggunakan Certainty Factor Dalam Mendiagnosa Kategori Tingkat Demam Berdarah - Rizaldi, Achmad; Voutama, Apriade; Susilawati, Susilawati (Generation Journal, 2021)
Dengue Fever is still a serious health problem and a major problem in the health sector in various parts of the world and also in Indonesia. This disease is an infectious disease and can infect all ages because there are still many people who still lack awareness in maintaining cleanliness to anticipate transmission. Data from the Ministry of Health of the Republic of Indonesia (Kemenkes RI) Indonesia recorded the number of people infected with Dengue Fever disease as many as 95,893 throughout 2020 and as many as 661 people died from this disease. The method used is using the certainty factor method where if it is interpreted this method will be used to help make a decision to diagnose the category of Dengue Fever level with a level of confidence in the form of a percentage of how much someone is infected with Dengue Fever in the existing category. The results obtained in the calculation of certainty factor get a result in the category of grade 1 of 98%, grade 2 of 98%, grade 3 of 99%, grade 4 of 99%. These results are enough to prove that this certainty factor method has a fairly high percentage level result.